5(5c-1)-1=20c+4

Simple and best practice solution for 5(5c-1)-1=20c+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(5c-1)-1=20c+4 equation:


Simplifying
5(5c + -1) + -1 = 20c + 4

Reorder the terms:
5(-1 + 5c) + -1 = 20c + 4
(-1 * 5 + 5c * 5) + -1 = 20c + 4
(-5 + 25c) + -1 = 20c + 4

Reorder the terms:
-5 + -1 + 25c = 20c + 4

Combine like terms: -5 + -1 = -6
-6 + 25c = 20c + 4

Reorder the terms:
-6 + 25c = 4 + 20c

Solving
-6 + 25c = 4 + 20c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-20c' to each side of the equation.
-6 + 25c + -20c = 4 + 20c + -20c

Combine like terms: 25c + -20c = 5c
-6 + 5c = 4 + 20c + -20c

Combine like terms: 20c + -20c = 0
-6 + 5c = 4 + 0
-6 + 5c = 4

Add '6' to each side of the equation.
-6 + 6 + 5c = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 5c = 4 + 6
5c = 4 + 6

Combine like terms: 4 + 6 = 10
5c = 10

Divide each side by '5'.
c = 2

Simplifying
c = 2

See similar equations:

| 4-3[q]=10 | | 65(2x-5)=180 | | Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 | | 53435+n=2888195 | | 4x-2(x-4)=-7+5x-6 |

Equations solver categories